ORALITY AND NOTATION OF KOREAN TRADITIONAL MUSIC: CHANGE AND CONTINUITY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Korean traditional music has primarily been transmitted orally. Teachers did not play instruments but sang melodies using a mnemonic system called Gu-eum («mouth tone»). Despite this oral tradition, Korea also has a rich history of music notation, especially in court and aristocratic music, where systems like Jeongganbo (a 15th-century mensural notation) were used. In the 20th century, Western influences brought changes to how music was taught and passed down. My research explores the transformation and continuity of oral and written transmission methods across different musical genres. While both Gu-eum and notations have been studied, few works offer an integrated perspective. Through interviews and literature review, I examined what has evolved and what persists. The findings show that Gu-eum still functions as a key communication tool in education, though it now plays a secondary role. Jeongganbo remains in use for classical music and is even applied in some folk traditions. This study highlights the enduring roles of both oral and notated systems and how they have adapted within the transmission of Korean traditional music.
Keywords: Korea, Gy-eum, notation, traditional music, oral transmission, orality